METHOD FOR CALCULATING RELIABILITY OF WATER RECYCLING - , В. Г., С. О. (Municipal economy of cities. Series: «Economy science», 2013)
Developed a method for calculating the reliability and maintainability of cooling systems of the circulation water system of industrial enterprises.